2020
DOI: 10.1177/2040620720966121
|View full text |Cite
|
Sign up to set email alerts
|

Serum ferritin and ECOG performance status predict the response and improve the prognostic value of IPSS or IPSS-R in patients with high-risk myelodysplastic syndromes and oligoblastic acute myeloid leukemia treated with 5-azacytidine: a retrospective analysis of the Hellenic national registry of myelodysplastic and hypoplastic syndromes

Abstract: Background: 5-azacytidine (5-AZA) improves survival of patients with higher-risk myelodysplastic syndromes (MDSs) and oligoblastic acute myeloid leukemia (AML); however, predictive factors for response and outcome have not been consistently studied. Methods: This study of the Hellenic MDS Study Group included 687 consecutive patients with higher-risk MDS and oligoblastic AML treated with 5-AZA. Results: The International Prognostic Scoring System (IPSS) revised version (IPSS-R), Eastern Cooperative Oncology Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
(57 reference statements)
2
3
0
Order By: Relevance
“…Evaluation of PFS according to patient subgroups revealed that patients diagnosed with versus without secondary AML, with an ECOG performance status ≥2 versus 0 or 1, with poor or intermediate versus favorable cytogenetic risk, or with CCI ≥1 versus 0 had shorter median PFS. These results are consistent with previous studies in which poor ECOG performance status and comorbidity index scores were associated with shorter median PFS [23].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Evaluation of PFS according to patient subgroups revealed that patients diagnosed with versus without secondary AML, with an ECOG performance status ≥2 versus 0 or 1, with poor or intermediate versus favorable cytogenetic risk, or with CCI ≥1 versus 0 had shorter median PFS. These results are consistent with previous studies in which poor ECOG performance status and comorbidity index scores were associated with shorter median PFS [23].…”
Section: Discussionsupporting
confidence: 93%
“…When evaluating OS in patient subgroups, we found that those diagnosed with versus without secondary AML, with an ECOG performance status ≥2 versus 0 or 1, with poor or intermediate versus favorable cytogenetic risk, or with CCI ≥1 versus 0 had a shorter median OS. Similar observations have been reported in previous studies [14, 23-25].…”
Section: Discussionsupporting
confidence: 93%
“…Its incorporation into risk stratification could help identify high-risk patients most likely to benefit from alternative therapeutic approaches. 48 , 49 …”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous studies in which poor ECOG performance status and comorbidity index scores were associated with shorter median PFS. 25 …”
Section: Discussionmentioning
confidence: 99%